A Review of a Collaborative Online International Learning - Annan, E.; Appiah-Kubi, P. (International Journal of Engineering Pedagogy, 2020)
Abstract—Globalization has exacerbated the need for engineers who are capable of working in a cross-cultural environment. Multinational companies continuously seek for engineers who are interculturally competent and capable of conducting business successfully in a cross-cultural environment. However, the skills required to be successful in a multicultural environment are difficult to be taught in the traditional classroom. One of the most effective approaches to acquiring intercultural competency skills is through experiential learning. It is, therefore, not surprising that most colleges all over the world are devoting resources towards the internationalization of their classrooms and the campus community. This ensures that students are provided with a diverse environment, so they can learn from, and about diverse cultures to enhance their intercultural competency skills. Another effective approach is the study abroad programs, which require students to travel to different countries. However, these approaches require a lot of resources that may not be available to the less fortunate students. Therefore, a more cost-effective approach, such as Collaborative Online International Learning (COIL), is receiving a lot of attention in recent years. In this study, some engineering technology students participated in a 8-week long COIL program with materials engineering students from different languacultural and geographical regions. This study reviews the results and compares the performance of the COIL students with those who were not involved in the study. It was observed that the COIL teams performed significantly better on the project work. In addition, 70% (of the 11 students from the University of Ghana) and 85% (of the 20 students from the University of Dayton) respectively reported that the collaboration was either effective or very effective
Research Article
Keywords: Collaborative learning; intercultural competence; project management; cooperative learning; COIL